Income support systems, labor market policies and labor supply: the German experience - Caliendo, Marco (Bonn, 2009)
"In view of the demographic trends, most EU countries face the problem of a declining work force in the future. Understanding the interaction between income support systems (such as unemployment benefits, social assistance, early retirement and pension systems) and total labor supply is of crucial importance to combat problems and ensure economic growth in the future. The German labor market has been plagued by high and persistent unemployment in the last two decades in combination with a relatively low labor force participation of women. This created a situation where labor market reforms were unavoidable. The speed and depth of the reforms are remarkable, mainly aimed at activating people by increasing their incentives to take up work. The aim of this paper is to give a brief overview of the German income support systems and labor market polices, their recent reforms and – where already possible – effects of these reforms. Overall, Germany seems to be on the right track. The recent reforms helped to tackle some labor market problems but also created high political unrest. It remains to be seen how future governments react to worsened economic conditions in light of these experiences. "